Evaluation of Impact Energy Absorption by Natural Fiber Composites in Motorcycle Helmets - Tatiana Barbosa de Andrade; Carlos Roberto Hall Barbosa; Rosana Medeiros Moreira; Edilvando Pereira Eufrazio; Elcio Cruz de Oliveira (Applied Sciences)
In response to the growing concerns regarding motorcyclists’ safety and advancements in the motorcycle industry, this study investigated the potential of natural fibers as a sustainable approach for enhancing helmet protection, thus replacing the traditional use of expanded polystyrene. Utilizing statistical tools such as the Shapiro–Wilk test, Chauvenet’s criterion, and the interquartile range, we compared the impact energy absorption of composites reinforced with natural fibers, including sugarcane bagasse, coconut, and sisal, added to expanded polyurethane prototypes. The results, evaluated through confidence intervals, indicated that composites reinforced with 5% sugarcane bagasse, 5% and 10% coconut, and 10% and 15% sisal exhibited significantly superior impact absorption performance compared to pure expanded polyurethane. Composites with agave sisalana fibers exhibited low variability and reliable performance, with the 10% concentration showing the best results. Sugarcane bagasse fiber demonstrated strong stability, especially at a 5% concentration. Coconut fiber performed well at both 5% and 10% concentrations but showed the greatest variability among the fibers tested. These findings underscore the potential of natural fibers in enhancing helmet safety and suggest promising directions for future research into the ideal composite materials for motorcycle helmets, an inquiry that is currently underway.